Envisioning a Just Response to the Catholic Clergy Sexual Abuse Crisis - Beste, Jennifer Erin (2021)
In this article, I argue that the only way Catholics will experience the conversion of heart necessary to engage in authentic Christian discipleship and respond justly to the clergy sexual abuse crisis is to enter empathetically into the traumatic reality of the crisis. Recognition of the degree to which clergy abuse harms victim-survivors and subverts the church’s purpose to be the body of Christ leads to the moral obligation to prioritize urgent action on two objectives: (1) solidarity with clergy sexual abuse survivors and (2) effective prevention of clergy sexual abuse globally.
Keywords: spiritual trauma; secondary victimization; posttraumatic stress disorder (PTSD); mediation of grace; Justice; ecclesiological mission; clergy child sexual abuse victim-survivors; clergy child sexual abuse; Catholic Church; abuse of power